2023
DOI: 10.1097/js9.0000000000000861
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of preoperative nutritional status for postoperative acute kidney injury in older patients undergoing major abdominal surgery: a retrospective cohort study

Rao Sun,
Zhiqiang Zhou,
Xinhua Li
et al.

Abstract: Background: The association between malnutrition and postoperative acute kidney injury (AKI) has not been well studied. In this study, we examined the association between preoperative nutritional status and postoperative AKI in older patients who underwent major abdominal surgery, as well as the predictive value of malnutrition for AKI. Materials and methods: We retrospectively included patients aged 65 or older who underwent major elective abdominal su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…A recent study found preoperative fasting protected against intestinal ischemia/reperfusion injury by modulating gut microbiota [207]. Our recent study also showed that preoperative nutritional status could predict postoperative renal injury [208]. However, until now, there is no sufficient evidence on whether IF influences the outcome of PND.…”
Section: Perioperative Neurocognitive Dysfunction (Pnd)mentioning
confidence: 78%
“…A recent study found preoperative fasting protected against intestinal ischemia/reperfusion injury by modulating gut microbiota [207]. Our recent study also showed that preoperative nutritional status could predict postoperative renal injury [208]. However, until now, there is no sufficient evidence on whether IF influences the outcome of PND.…”
Section: Perioperative Neurocognitive Dysfunction (Pnd)mentioning
confidence: 78%
“…However, serum creatinine levels may underestimate renal function impairment in populations with diminished muscle mass 41 , such as those suffering from sarcopenia or malnutrition. It has been demonstrated that these populations are at an increased risk of AKI 2 , 42 . In a recent study, a U-shaped relationship has been demonstrated between preoperative creatinine and postoperative AKI 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a common surgical complication characterized by a rapid decline in renal function 1 , 2 . Patients with AKI are at an increased risk of developing chronic kidney disease and end-stage renal disease, which has been associated with an increased risk of morbidity, mortality, and financial burdens 3 5 .…”
Section: Introductionmentioning
confidence: 99%